ChemInform Abstract: Rapid and Efficient Cascade Synthesis of 2‐Amino‐4(3H)‐quinazolinones over an in situ‐Generated Heterogeneous CuCO3—K2CO3 Nanocomposite. Issue 43 (7th October 2016) - Thakur, Maheshwar S.; Nayal, Onkar S.; Bhatt, Vinod; Sharma, Sushila; Kumar, Neeraj
Abstract: The nanocomposite catalyzed cascade reaction of 2‐halobenzoic acids and guanidines or amidines proceeds rapidly in air without the addition of a ligand or additive to form quinazoline derivatives.